2017
DOI: 10.1002/14651858.cd011479.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Personalised digital interventions for reducing hazardous and harmful alcohol consumption in community-dwelling populations

Abstract: There is moderate-quality evidence that digital interventions may lower alcohol consumption, with an average reduction of up to three (UK) standard drinks per week compared to control participants. Substantial heterogeneity and risk of performance and publication bias may mean the reduction was lower. Low-quality evidence from fewer studies suggested there may be little or no difference in impact on alcohol consumption between digital and face-to-face interventions.The BCTs of behaviour substitution, problem s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
250
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(282 citation statements)
references
References 228 publications
17
250
0
4
Order By: Relevance
“…137 Interventions delivered via computers and smart phones can also reduce alcohol consumption in hazardous and harmful drinkers. 138 In the hospital setting, a recent study has shown it is feasible to screen all medical admissions to identify individuals at risk of alcohol abuse, to prompt an early brief intervention or referral to an alcohol specialist nurse. 139 Once admitted, alcohol advice delivered by a liver specialist can lead to a high proportion of patients reducing their intake.…”
Section: Evidence For Individual Interventionsmentioning
confidence: 99%
“…137 Interventions delivered via computers and smart phones can also reduce alcohol consumption in hazardous and harmful drinkers. 138 In the hospital setting, a recent study has shown it is feasible to screen all medical admissions to identify individuals at risk of alcohol abuse, to prompt an early brief intervention or referral to an alcohol specialist nurse. 139 Once admitted, alcohol advice delivered by a liver specialist can lead to a high proportion of patients reducing their intake.…”
Section: Evidence For Individual Interventionsmentioning
confidence: 99%
“…Credibility of health information disseminated by all tweets may be called into question but, in particular, the credibility of tweets by information intermediaries and non-professionals is more questionable as the risk of health misinformation is inherently higher (8,10). Provision of information from a credible source ("Presenting verbal or visual communication from a credible source…"(21)) has been shown to be an effective behaviour change technique, particularly in digital interventions (21,22). However, on Twitter, credibility is essentially an individual judgement by the follower, and health misinformation from information intermediaries (who present themselves as professionals) is at particular risk of being viewed by the general public as evidence-based science.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that impacts are sustained, researchers should consider the wider technological, human resource and health system needs .Harder et al . add to the rapidly growing literature supporting the use of digital technology to reduce heavy drinking . The authors find that motivational interviewing‐based alcohol interventions delivered by mobile phone perform as well as their face‐to‐face alternatives, at least in the short term.…”
mentioning
confidence: 88%